(untitled) (Journal of Vocational Innovation, Achievement and Education, 2025)
The maintenance of larvae in hatcheries must consider seed quality, one aspect of which involves implementing standard operating procedures for appropriate feeding. Thalassiosira sp. has a complex nutritional content that supports growth, making it selected as a natural feed for vaname shrimp larvae. This final project aims to describe the technique of culturing Thalassiosira sp. and to identify obstacles as well actions that can be taken during the Thalassiosira sp. culturing process. Method. The culturing stages are conducted in a stepwise manner, starting from the smallest volume, namely from laboratory scale, intermediate scale, to mass scale. Results. The peak population in the bottle container occurred on day 3, reaching 940,000 cells/ml. This was followed by culturing in gallon 1 media at 590,000 cells/ml and gallon 2 media at 400,000 cells/ml. Subsequently, at the intermediate scale, the peak population occurred on day 2 with 81,000 cells/ml, and finally at the mass scale, it reached 162,000 cells/ml on day 2. Conclusion. The harvesting process is conducted during the logarithmic phase to obtain maximum biomass